Atomic‐Scale Determination of Active Facets on the MoVTeNb Oxide M1 Phase and Their Intrinsic Catalytic Activity for Ethane Oxidative Dehydrogenation. (16th March 2016) - Melzer, Daniel; Xu, Pinghong; Hartmann, Daniela; Zhu, Yuanyuan; Browning, Nigel D.; Sanchez‐Sanchez, Maricruz; Lercher, Johannes A.
Abstract: Aberration‐corrected high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) has been used to image the basal 001 plane of the catalytically relevant M1 phase in MoVTeNb complex oxides. Facets 010, 120, and 210 are identified as the most frequent lateral termination planes of the crystals. Combination of STEM with He ion microscopy (HIM) images, Rietveld analysis, and kinetic tests reveals that the activation of ethane is correlated to the availability of facets 001, 120, and 210 at the surface of M1 crystals. The lateral facets 120 and 210 expose crystalline positions related to the typical active centers described for propane oxidation. Conversely, the low activity of the facet 010 is attributed to its configuration, consisting of only stable M6 O21 units connected by a single octahedron. Thus, we quantitatively demonstrated that differences in catalytic activity among M1 samples of equal chemical composition depend primarily on the morphology of the particles, which determines the predominant terminating facets.